Low-shrinkage low-viscosity ultrahigh-strength concrete

Through specific formulas and processes, combined with efficient stirring and precise control of proportions, the problems of shrinkage cracking and high viscosity of ultra-high strength concrete in applications are solved, and the concrete performance of low shrinkage, low viscosity and ultra-high strength is achieved.

CN119490340AInactive Publication Date: 2025-02-21HENAN XINYE SUPPLY CHAIN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411783199.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119490340A_ABST
    Figure CN119490340A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of constructional engineering materials, and discloses low-shrinkage low-viscosity ultrahigh-strength concrete. The concrete comprises the following raw materials: Portland cement, mineral powder, limestone powder, fly ash, medium sand, basalt macadam, fly ash floating beads, metakaolin, fine steel fibers, a polycarboxylic acid superplasticizer, a calcium sulphoaluminate-calcium oxide expanding agent, acrylic acid modified chlorinated polyether resin, modified epoxy resin, sodium polyacrylate, unsaturated monobasic acid, phosphogypsum and S95-grade slag. According to the invention, through a specific formula and process, the problems of shrinkage cracking and difficult pumping of ultrahigh-strength concrete in application are effectively solved; the concrete has the advantages of high strength, high corrosion resistance and durability, capability of reducing the structure size, reducing the structure self weight, reducing the structure maintenance cost and reconstruction cost and the like; the concrete has outstanding application advantages in large-scale projects such as super high-rise buildings, cross-sea bridges and offshore oil production platforms, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building engineering materials, and in particular relates to a low-shrinkage, low-viscosity and ultra-high-strength concrete. Background Art

[0002] High-strength and high-performance concrete has become a concrete technology that the construction industry focuses on and pays attention to due to its high strength, high corrosion resistance and durability. It can reduce structural size, reduce structural deadweight, save land, reduce energy consumption, and reduce structural maintenance and reconstruction costs. As architectural design develops in the direction of high-rise, super-high-rise, large-span, underground, and adaptable to harsh environments, high-strength and ultra-high-strength high-performance concrete have shown significant application advantages in large-scale projects such as super-high-rise buildings, cross-sea bridges, and offshore oil platforms. Ultra-high-strength concrete, that is, concrete with a cubic compressive strength of more than 100MPa, has excellent performance, but due to its high cementitious material dosage (600-700kg / m 3 ), low water-binder ratio (0.18-0.21) and high admixture dosage (18-25kg / m 3 ), and added super-active material silica fume, resulting in high hydration heat, severe shrinkage cracking, and its high viscosity makes pumping difficult. Although technological development has alleviated some of the problems of ultra-high strength concrete to a certain extent, such as Chinese patent CN103524093A using the characteristics of phosphorus slag to delay cement hydration, reduce hydration heat and reduce temperature cracks, it has not yet effectively solved its large shrinkage and high viscosity problems. Summary of the invention

[0003] The object of the present invention is to provide a low shrinkage, low viscosity and ultra-high strength concrete to solve the problems raised in the above background technology.

[0004] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: a low-shrinkage, low-viscosity, ultra-high-strength concrete, which comprises the following raw materials in parts by weight: silicate cement: 20-30 parts, mineral powder: 10-15 parts, limestone powder: 10-20 parts, fly ash: 10-15 parts, medium sand: 20-25 parts, basalt crushed stone: 10-15 parts, fly ash floating beads: 20-30 parts, metakaolin: 10-15 parts, fine steel fiber: 8-13 parts, polycarboxylic acid high-efficiency water reducing agent: 1-3 parts, calcium sulfoaluminate-calcium oxide expansion agent: 0.5-5 parts, acrylic acid modified chloroether resin: 10-15 parts, modified epoxy resin: 8-12 parts, polyacrylic acid sodium salt: 8-10 parts, unsaturated monobasic acid: 2-15 parts, phosphogypsum: 8-12 parts, and S95 grade slag 10-15 parts.

[0005] Preferably, the concrete includes the following specific components: silicate cement: 25 parts, mineral powder: 13 parts, limestone powder: 15 parts, fly ash: 13 parts, medium sand: 23 parts, basalt crushed stone: 12 parts, fly ash floating beads: 24 parts, metakaolin: 13 parts, fine steel fiber: 10 parts, polycarboxylic acid high-efficiency water reducing agent: 2 parts, calcium sulfoaluminate-calcium oxide expansion agent: 3 parts, acrylic acid modified chloroether resin: 12 parts, modified epoxy resin: 10 parts, polyacrylic acid sodium salt: 9 parts, unsaturated monobasic acid: 10 parts, phosphogypsum: 10 parts, and S95 grade slag 12 parts.

[0006] Preferably, the method for preparing concrete based on the above concrete formula is:

[0007] Step 1, raw material preparation: according to Portland cement: 25 parts, mineral powder: 13 parts, limestone powder: 15 parts, fly ash: 13 parts, medium sand: 23 parts, basalt crushed stone: 12 parts, fly ash floating beads: 24 parts, metakaolin: 13 parts, fine steel fiber: 10 parts, polycarboxylic acid high-efficiency water reducing agent: 2 parts, calcium sulfoaluminate-calcium oxide expansion agent: 3 parts, acrylic acid modified chloroether resin: 12 parts, modified epoxy resin: 10 parts, polyacrylic acid sodium salt: 9 parts, unsaturated monobasic acid: 10 parts, phosphogypsum: 10 parts, S95 grade slag 12 parts, accurately weigh each raw material according to the ratio;

[0008] Step 2, mixing and stirring: Mix silicate cement, mineral powder, limestone powder, fly ash, and metakaolin evenly, then add medium sand, basalt crushed stone, fly ash floating beads, polycarboxylic acid high-efficiency water reducer, and calcium sulfoaluminate-calcium oxide expansion agent, and use a high-efficiency mixer for preliminary mixing;

[0009] Step 3, adding resin and fiber: gradually add acrylic modified chloroether resin, modified epoxy resin and fine steel fiber during stirring to ensure uniform dispersion;

[0010] Step 4: Adjusting viscosity and fluidity: adjusting the viscosity and fluidity of the concrete by adding sodium polyacrylate and unsaturated monobasic acid;

[0011] Step 5: Final mixing and pouring: Continue mixing until all ingredients are fully blended to form a uniform concrete slurry, followed by pouring;

[0012] Step 6. Maintenance: Perform maintenance according to standard maintenance procedures.

[0013] Preferably, the specific steps of mixing and stirring in step 2 are:

[0014] A1, preliminary mixing: put silicate cement, mineral powder, limestone powder, fly ash, and kaolin powder into a high-efficiency mixer for preliminary mixing. The mixing time is generally 1-2 minutes to ensure that the powder materials are evenly distributed;

[0015] A2, adding aggregates and admixtures: continue to add medium sand, basalt crushed stone, fly ash beads, collectively referred to as aggregates, and polycarboxylic acid high-efficiency water reducer and expansion agent, collectively referred to as admixtures, into the mixer; during the mixing process, the mixing speed and time should be properly controlled to avoid excessive wear of the mixer by the aggregates and ensure that the admixtures can be evenly dispersed in the concrete.

[0016] Preferably, the specific steps of adding resin and fiber in step 3 are:

[0017] B1, resin addition: During the mixing process, gradually add acrylic modified chloroether resin, modified epoxy resin and other resin materials; the resin should be added evenly and slowly to avoid excessive local concentration leading to uneven concrete performance;

[0018] B2, Fiber addition: Fine steel fibers are then added. The addition of steel fibers should also be uniform and slow to ensure their uniform distribution in the concrete; the amount of steel fibers added should be adjusted according to specific needs to improve the crack resistance and toughness of the concrete.

[0019] Preferably, the specific steps of adjusting the viscosity and fluidity in step 4 are:

[0020] C1, adding sodium polyacrylate: adding an appropriate amount of sodium polyacrylate to adjust the viscosity and fluidity of the concrete; sodium polyacrylate can increase the water retention and workability of the concrete, making it easier to pump and construct;

[0021] C2, adding unsaturated monobasic acid: Unsaturated monobasic acid adjusts the pH value inside the concrete and promotes the chemical reaction between the components; at the same time, it can further improve the fluidity of the concrete and make it more uniform.

[0022] Preferably, the specific steps in the final mixing and pouring of step 5 are:

[0023] D1, after all raw materials and admixtures are added, continue stirring for 2-3 minutes to ensure that all ingredients are fully blended to form a uniform concrete slurry;

[0024] D2, pouring operation: quickly pour the mixed concrete slurry into the mold or construction site for pouring; during the pouring process, attention should be paid to controlling the pouring speed and vibration intensity to avoid bubbles and defects in the concrete.

[0025] Preferably, in the step 4 of adjusting the viscosity and fluidity, the addition amount of polyacrylic acid sodium salt and unsaturated monobasic acid is precisely controlled to achieve an optimal balance between the viscosity and fluidity of the concrete.

[0026] Preferably, based on the above application of concrete: the concrete has the characteristics of low shrinkage, low viscosity and ultra-high strength, and is suitable for the construction of high-rise buildings, bridges, tunnels and large infrastructure, as well as the manufacture of precision structural parts with extremely high requirements on material properties.

[0027] The beneficial effects of the present invention are as follows:

[0028] Low shrinkage and low viscosity: Through a specific formula and process, the concrete prepared by the present invention has the characteristics of low shrinkage and low viscosity. The precise proportion of basic raw materials such as silicate cement, mineral powder, limestone powder, fly ash, medium sand, basalt crushed stone, etc. in the formula, supplemented by the addition of lightweight and high-strength materials such as fly ash beads and metakaolin, and the reinforcement of fine steel fibers, effectively solves the shrinkage cracking problem of ultra-high-strength concrete in application. At the same time, the addition of polycarboxylic acid high-efficiency water-reducing agent significantly reduces the viscosity of concrete, improves its fluidity, and solves the problem of difficult pumping.

[0029] High strength and high performance: This concrete not only has high strength, but also has the advantages of high corrosion resistance and durability. The appropriate addition of calcium sulfoaluminate-calcium oxide expansion agent further improves the volume stability and strength of concrete. The composite use of acrylic modified chloroether resin and modified epoxy resin enhances the chemical corrosion resistance of concrete, allowing the concrete to maintain good performance in harsh environments. These characteristics enable concrete to reduce structural size, reduce structural deadweight, save land, reduce energy consumption, and significantly reduce structural maintenance and reconstruction costs.

[0030] Green and environmentally friendly: The recycling of waste concrete is specifically mentioned in the raw materials. It is prepared through advanced waste concrete separation equipment, which not only reduces the generation of construction waste, but also realizes the recycling of resources, which is in line with the current concept of green environmental protection and sustainable development.

[0031] Broad application prospects: With its low shrinkage, low viscosity, high strength, high performance and green environmental protection characteristics, this concrete has shown outstanding application advantages in large-scale projects such as super high-rise buildings, cross-sea bridges, and offshore oil platforms. Its excellent performance ensures the stability and durability of engineering structures, providing a solid and reliable foundation for various large-scale projects, and therefore has extremely broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a simplified diagram of the preparation process of low shrinkage, low viscosity and ultra-high strength concrete. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] like Figure 1 As shown, an embodiment of the present invention provides a low shrinkage, low viscosity and ultra-high strength concrete, which includes the following raw materials in parts by weight: silicate cement: 20-30 parts, mineral powder: 10-15 parts, limestone powder: 10-20 parts, fly ash: 10-15 parts, medium sand: 20-25 parts, basalt crushed stone: 10-15 parts, fly ash floating beads: 20-30 parts, metakaolin: 10-15 parts, fine steel fiber: 8-13 parts, polycarboxylic acid high-efficiency water reducing agent: 1-3 parts, calcium sulfoaluminate-calcium oxide expansion agent: 0.5-5 parts, acrylic acid modified chloroether resin: 10-15 parts, modified epoxy resin: 8-12 parts, polyacrylic acid sodium salt: 8-10 parts, unsaturated monobasic acid: 2-15 parts, phosphogypsum: 8-12 parts, S95 grade slag 10-15 parts.

[0035] Among them, the concrete includes the following specific components: silicate cement: 25 parts, mineral powder: 13 parts, limestone powder: 15 parts, fly ash: 13 parts, medium sand: 23 parts, basalt crushed stone: 12 parts, fly ash floating beads: 24 parts, metakaolin: 13 parts, fine steel fiber: 10 parts, polycarboxylic acid high-efficiency water reducing agent: 2 parts, calcium sulfoaluminate-calcium oxide expansion agent: 3 parts, acrylic acid modified chloroether resin: 12 parts, modified epoxy resin: 10 parts, polyacrylic acid sodium salt: 9 parts, unsaturated monobasic acid: 10 parts, phosphogypsum: 10 parts, and S95 grade slag 12 parts.

[0036] Among them, the concrete preparation method based on the above concrete formula is:

[0037] Step 1, raw material preparation: according to Portland cement: 25 parts, mineral powder: 13 parts, limestone powder: 15 parts, fly ash: 13 parts, medium sand: 23 parts, basalt crushed stone: 12 parts, fly ash floating beads: 24 parts, metakaolin: 13 parts, fine steel fiber: 10 parts, polycarboxylic acid high-efficiency water reducing agent: 2 parts, calcium sulfoaluminate-calcium oxide expansion agent: 3 parts, acrylic acid modified chloroether resin: 12 parts, modified epoxy resin: 10 parts, polyacrylic acid sodium salt: 9 parts, unsaturated monobasic acid: 10 parts, phosphogypsum: 10 parts, S95 grade slag 12 parts, accurately weigh each raw material according to the ratio;

[0038] Step 2, mixing and stirring: Mix silicate cement, mineral powder, limestone powder, fly ash, and metakaolin evenly, then add medium sand, basalt crushed stone, fly ash floating beads, polycarboxylic acid high-efficiency water reducer, and calcium sulfoaluminate-calcium oxide expansion agent, and use a high-efficiency mixer for preliminary mixing;

[0039] Step 3, adding resin and fiber: gradually add acrylic modified chloroether resin, modified epoxy resin and fine steel fiber during stirring to ensure uniform dispersion;

[0040] Step 4: Adjusting viscosity and fluidity: adjusting the viscosity and fluidity of the concrete by adding sodium polyacrylate and unsaturated monobasic acid;

[0041] Step 5: Final mixing and pouring: Continue mixing until all ingredients are fully blended to form a uniform concrete slurry, followed by pouring;

[0042] Step 6. Maintenance: Perform maintenance according to standard maintenance procedures.

[0043] Standard curing: After pouring, curing shall be carried out according to the standard curing procedure; during curing, suitable temperature and humidity conditions shall be maintained to promote the hardening and strength development of concrete;

[0044] Strength test: After the curing period, the strength test and other performance tests of the concrete are carried out; based on the test results, it is evaluated whether the performance of the concrete meets the design requirements and usage needs.

[0045] The specific steps of mixing and stirring in step 2 are:

[0046] A1, preliminary mixing: put silicate cement, mineral powder, limestone powder, fly ash, and kaolin powder into a high-efficiency mixer for preliminary mixing. The mixing time is generally 1-2 minutes to ensure that the powder materials are evenly distributed;

[0047] A2, adding aggregates and admixtures: continue to add medium sand, basalt crushed stone, fly ash beads, collectively referred to as aggregates, and polycarboxylic acid high-efficiency water reducer and expansion agent, collectively referred to as admixtures, into the mixer; during the mixing process, the mixing speed and time should be properly controlled to avoid excessive wear of the mixer by the aggregates and ensure that the admixtures can be evenly dispersed in the concrete.

[0048] Among them, the specific steps of adding resin and fiber in step 3 are:

[0049] B1, resin addition: During the mixing process, gradually add acrylic modified chloroether resin, modified epoxy resin and other resin materials; the resin should be added evenly and slowly to avoid excessive local concentration leading to uneven concrete performance;

[0050] B2, Fiber addition: Fine steel fibers are then added. The addition of steel fibers should also be uniform and slow to ensure their uniform distribution in the concrete; the amount of steel fibers added should be adjusted according to specific needs to improve the crack resistance and toughness of the concrete.

[0051] Among them, the specific steps in step 4 of adjusting viscosity and fluidity are:

[0052] C1, adding sodium polyacrylate: In order to adjust the viscosity and fluidity of concrete, add an appropriate amount of sodium polyacrylate to adjust the viscosity and fluidity of concrete; sodium polyacrylate can increase the water retention and workability of concrete, making it easier to pump and construct;

[0053] C2, adding unsaturated monobasic acid: Unsaturated monobasic acid adjusts the pH value inside the concrete and promotes the chemical reaction between the components; at the same time, it can further improve the fluidity of the concrete and make it more uniform.

[0054] Among them, the specific steps in the final mixing and pouring of step 5 are:

[0055] D1, after all raw materials and admixtures are added, continue stirring for 2-3 minutes to ensure that all ingredients are fully blended to form a uniform concrete slurry;

[0056] D2, pouring operation: quickly pour the mixed concrete slurry into the mold or construction site for pouring; during the pouring process, attention should be paid to controlling the pouring speed and vibration intensity to avoid bubbles and defects in the concrete.

[0057] Among them, in step 4 of adjusting viscosity and fluidity, the optimal balance between concrete viscosity and fluidity is achieved by precisely controlling the added amounts of sodium polyacrylate and unsaturated monobasic acid.

[0058] Among them, based on the above application of concrete: this concrete has the characteristics of low shrinkage, low viscosity and ultra-high strength, and is suitable for the construction of high-rise buildings, bridges, tunnels and large-scale infrastructure, as well as the manufacture of precision structural parts with extremely high requirements for material performance.

[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A low shrinkage, low viscosity, ultra-high strength concrete, characterized by: The concrete comprises the following raw materials in parts by weight: 20-30 parts of silicate cement, 10-15 parts of mineral powder, 10-20 parts of limestone powder, 10-15 parts of fly ash, 20-25 parts of medium sand, 10-15 parts of basalt crushed stone, 20-30 parts of fly ash floating beads, 10-15 parts of metakaolin, 8-13 parts of fine steel fiber, 1-3 parts of polycarboxylic acid high-efficiency water reducing agent, 0.5-5 parts of calcium sulfoaluminate-calcium oxide expansion agent, 10-15 parts of acrylic acid modified chloroether resin, 8-12 parts of modified epoxy resin, 8-10 parts of polyacrylic acid sodium salt, 2-15 parts of unsaturated monobasic acid, 8-12 parts of phosphogypsum and 10-15 parts of S95 grade slag.

2. The low shrinkage, low viscosity and ultra-high strength concrete according to claim 1, characterized in that: The concrete includes the following specific components: silicate cement: 25 parts, mineral powder: 13 parts, limestone powder: 15 parts, fly ash: 13 parts, medium sand: 23 parts, basalt crushed stone: 12 parts, fly ash floating beads: 24 parts, metakaolin: 13 parts, fine steel fiber: 10 parts, polycarboxylic acid high-efficiency water reducing agent: 2 parts, calcium sulfoaluminate-calcium oxide expansion agent: 3 parts, acrylic acid modified chloroether resin: 12 parts, modified epoxy resin: 10 parts, polyacrylic acid sodium salt: 9 parts, unsaturated monobasic acid: 10 parts, phosphogypsum: 10 parts, and S95 grade slag 12 parts.

3. The low shrinkage, low viscosity and ultra-high strength concrete according to claim 2, characterized in that: The concrete preparation method based on the above concrete formula is: Step 1, raw material preparation: according to Portland cement: 25 parts, mineral powder: 13 parts, limestone powder: 15 parts, fly ash: 13 parts, medium sand: 23 parts, basalt crushed stone: 12 parts, fly ash floating beads: 24 parts, metakaolin: 13 parts, fine steel fiber: 10 parts, polycarboxylic acid high-efficiency water reducing agent: 2 parts, calcium sulfoaluminate-calcium oxide expansion agent: 3 parts, acrylic acid modified chloroether resin: 12 parts, modified epoxy resin: 10 parts, polyacrylic acid sodium salt: 9 parts, unsaturated monobasic acid: 10 parts, phosphogypsum: 10 parts, S95 grade slag 12 parts, accurately weigh each raw material according to the ratio; Step 2, mixing and stirring: Mix silicate cement, mineral powder, limestone powder, fly ash, and metakaolin evenly, then add medium sand, basalt crushed stone, fly ash floating beads, polycarboxylic acid high-efficiency water reducer, and calcium sulfoaluminate-calcium oxide expansion agent, and use a high-efficiency mixer for preliminary mixing; Step 3, adding resin and fiber: gradually add acrylic modified chloroether resin, modified epoxy resin and fine steel fiber during stirring to ensure uniform dispersion; Step 4: Adjusting viscosity and fluidity: adjusting the viscosity and fluidity of the concrete by adding sodium polyacrylate and unsaturated monobasic acid; Step 5: Final mixing and pouring: Continue mixing until all ingredients are fully blended to form a uniform concrete slurry, followed by pouring; Step 6. Maintenance: Perform maintenance according to standard maintenance procedures.

4. The low shrinkage, low viscosity and ultra-high strength concrete according to claim 3, characterized in that: The specific steps of mixing and stirring in step 2 are: A1, preliminary mixing: put silicate cement, mineral powder, limestone powder, fly ash, and kaolin powder into a high-efficiency mixer for preliminary mixing. The mixing time is generally 1-2 minutes to ensure that the powder materials are evenly distributed; A2, adding aggregates and admixtures: continue to add medium sand, basalt crushed stone, fly ash beads, collectively referred to as aggregates, and polycarboxylic acid high-efficiency water reducer and expansion agent, collectively referred to as admixtures, into the mixer; during the mixing process, the mixing speed and time should be properly controlled to avoid excessive wear of the mixer by the aggregates and ensure that the admixtures can be evenly dispersed in the concrete.

5. The low shrinkage, low viscosity and ultra-high strength concrete according to claim 3, characterized in that: The specific steps of adding resin and fiber in step 3 are: B1, resin addition: During the mixing process, gradually add acrylic modified chloroether resin and modified epoxy resin; the resin should be added evenly and slowly to avoid excessive local concentration leading to uneven concrete performance; B2, Fiber addition: Fine steel fibers are then added. The addition of steel fibers should also be uniform and slow to ensure their uniform distribution in the concrete; the amount of steel fibers added should be adjusted according to specific needs to improve the crack resistance and toughness of the concrete.

6. The low shrinkage, low viscosity and ultra-high strength concrete according to claim 3, characterized in that: The specific steps of adjusting the viscosity and fluidity in step 4 are as follows: C1, adding sodium polyacrylate: adding an appropriate amount of sodium polyacrylate to adjust the viscosity and fluidity of the concrete; sodium polyacrylate can increase the water retention and workability of the concrete, making it easier to pump and construct; C2, adding unsaturated monobasic acid: Unsaturated monobasic acid adjusts the pH value inside the concrete and promotes the chemical reaction between the components; at the same time, it can further improve the fluidity of the concrete and make it more uniform.

7. The low shrinkage, low viscosity and ultra-high strength concrete according to claim 3, characterized in that: The specific steps in the final mixing and pouring of step 5 are as follows: D1, after all raw materials and admixtures are added, continue stirring for 2-3 minutes to ensure that all ingredients are fully blended to form a uniform concrete slurry; D2, pouring operation: quickly pour the mixed concrete slurry into the mold or construction site for pouring; during the pouring process, attention should be paid to controlling the pouring speed and vibration intensity to avoid bubbles and defects in the concrete.

8. The low shrinkage, low viscosity and ultra-high strength concrete according to claim 3, characterized in that: In the step 4 of adjusting the viscosity and fluidity, the optimal balance between the viscosity and fluidity of the concrete is achieved by precisely controlling the added amounts of sodium polyacrylate and unsaturated monobasic acid.

9. The low shrinkage, low viscosity and ultra-high strength concrete according to claims 1-8, characterized in that: Based on the above applications of concrete: This concrete has the characteristics of low shrinkage, low viscosity and ultra-high strength, and is suitable for the construction of high-rise buildings, bridges, tunnels and large-scale infrastructure, as well as the manufacture of precision structural parts with extremely high requirements for material properties.

Citation Information

Patent Citations

  • Ultrahigh strength concrete

    CN103524093A